PENGEMBANGAN MODEL PERSEDIAAN PRODUK BERTIPE NEWSBOY DENGAN MENGAKOMODASIKAN PERUBAHAN HARGA JUAL TERHADAP WAKTU DAN DISKON KUANTITAS - Edy Sianto, Martinus
Abstract: In this theses classical newsboy is developed. This model accommodates different prices during the season and quantity discount from supplier. The model is approached in three sections: deterministic, probabilistic and discount. The deterministic section is developed to determine time to change the price and mean of demands in each period, by accommodating demand function. The demand of product is multivariate function of price and time. Probabilistic section determines optimal quantity order to accommodate probabilistic nature of newsboy problems. An algorithm for discount quantity problem is developed in the discount section. Application of the model is presented in an example. Sensitivity analysis is conducted to reveal model characteristics. The model developed shows greater expected profit then classical model.